Making minds : how theory of mind develops - Wellman, Henry M. (Oxford series in cognitive development., 2014)
This book provides a comprehensive examination of how theory of mind develops. Building on previous work, this book pulls together' all that we have learned in the past 25 years to make sense of this powerful everyday theory. This book includes chapters on evolution and the brain bases of theory of mind; updated treatments and explanations of theory; infant theory of mind as the platform for developments in later childhood; and later developments from middle childhood to adulthood, including how we understand extraordinary minds such as those that belong to gods, superheroes, or supernatural beings.